2009
DOI: 10.1590/s1806-37132009000800003
|View full text |Cite
|
Sign up to set email alerts
|

Influência dos parâmetros funcionais respiratórios na qualidade de vida de pacientes com DPOC

Abstract: Objective: To determine the quality of life of COPD patients by using the Medical Outcomes 36-item Short-Form Survey (SF-36) and the Saint George's Respiratory Questionnaire (SGRQ), correlating the scores with respiratory function parameters. Methods: This was a cross-sectional study involving 42 COPD patients. We used the SGRQ (a specific questionnaire) and the SF-36 (a general questionnaire), together with their component summaries, in order to determine the quality of life of these patients. The functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 27 publications
1
9
1
2
Order By: Relevance
“…(23) In the present study, the oxygen flow rate at rest and the nocturnal oxygen flow rate were because pain is a symptom that is not specific to the clinical profile of COPD. (8)(9)(10)(11) Contrary to the literature, which shows a predominance of males among COPD patients in less developed countries, our study sample followed the trend seen in studies conducted in developed countries and reporting a similar prevalence of COPD in males and females, which can be explained by changes in smoking patterns. (2,12) In addition, no significant correlation was found between gender and the SF-36 domains, which is consistent with the findings of other studies.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…(23) In the present study, the oxygen flow rate at rest and the nocturnal oxygen flow rate were because pain is a symptom that is not specific to the clinical profile of COPD. (8)(9)(10)(11) Contrary to the literature, which shows a predominance of males among COPD patients in less developed countries, our study sample followed the trend seen in studies conducted in developed countries and reporting a similar prevalence of COPD in males and females, which can be explained by changes in smoking patterns. (2,12) In addition, no significant correlation was found between gender and the SF-36 domains, which is consistent with the findings of other studies.…”
Section: Discussioncontrasting
confidence: 57%
“…(9) In other studies involving similar samples, major changes have also been found in those two domains, which indicates that patients with those characteristics have physical limitations that compromise the performance of ADL. (10,11) In the present study, the bodily pain domain, despite being impaired, had the highest mean score (61.2) of all eight SF-36 domains, probably All patients were on LTOT. The patients with mild or moderate COPD were hypoxemic and showed evidence of cor pulmonale, as defined by the GOLD criteria.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Although pulmonary function impairment has been found to be associated with poor HRQOL in some studies, most studies have been conducted among small, clinical populations and not the general population [9-12]. In addition, most research has not included data on respiratory symptoms, relying primarily on spirometric measures of disease severity [10]. Also, most studies have not evaluated the association between respiratory symptoms and HRQOL septely from pulmonary function; therefore they have not been able to assess whether poor HRQOL was attributable to impaired pulmonary function rather than respiratory symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Pereira et al (26) conducted a study with COPD patients (2009) and found no correlation between the 6-MWT and the SF-36 PSS (physical summary scale) and MHSS (mental health summary scale). However, differently from our study and from other studies discussed previously, these authors have used the summary scales instead of the eight individual scales.…”
Section: (Conclusion)mentioning
confidence: 99%